The transcription factor VpCRZ1 is required for fruiting body formation and pathogenicity in Valsa pyri. (June 2016) - He, Feng; Zhang, Xiong; Mafurah, Joseph Juma; Zhang, Meixiang; Qian, Guoliang; Wang, Rongbo; Safdar, Asma; Yang, Xiaolei; Liu, Fengquan; Dou, Daolong
Abstract: Valsa pyri is a fatal pathogenic fungus that causes pear and apple canker disease. To date, its cellular development and pathogenicity have been poorly understood. In this study, a V . pyri Ca 2+ /calcineurin-dependent transcription factor CRZ1 (VpCRZ1) is identified and functionally characterized. The △VpCRZ1 mutant exhibits impaired pathogenicity and is no longer able to form fruiting body. Interestingly, this mutant also exhibits enhanced pigment deposition and increased resistance to cell wall perturbing agents including SDS, Congo red and calcofluor white (CFW). The expression levels of Congo red resistance genes ( VpRCR1 and VpRCR2 ) and chitin synthetase genes ( VpCHS2 and VpCHS6 ) are upregulated in the △VpCRZ1 mutant compared to the wild type. Furthermore, We show that a VpCRZ1: eGFP fusion protein localizes to the nucleus in a Ca 2+ -dependent manner similar to its homologs in other fungi, and that the VpFKS1, VpPMC1, VpPMC2, VpPMR1, and VpPMA1 genes are regulated by VpCRZ1 in response to Ca 2+ levels. Together, these results suggest that VpCRZ1 is a Ca 2+ -dependent transcription factor and required for regulating mycelial morphology, fruiting body formation, and virulence of this important pear and apple pathogen. Highlights: This is the first experimental research for gene's function and characterization in Valsa pyri. The VpCRZ1 is required for virulence and fruiting body formation. VpCRZ1 negatively control the pigment deposition and cell wall integrity by regulating expression of genes.